A Review on Nanoparticle-mediated Drug Delivery for Targeted Cancer Therapy: Impact of Lyophilization on Formulation Stability - Vyas, Dhruvi; Panjwani, Drishti; Patel, Shruti; Ahlawat, Priyanka; Dharamsi, Abhay; Patel, Laxmanbhai. Dungarbhai; Patel, Asha (Current Drug Therapy, 2025)
Cancer is a leading cause of death worldwide. Despite continuous efforts made to improve the shortcomings of the conventional approach, it remains formidable with high mortality. Contrary to the traditional approach, targeted therapies have emerged as a solution to fight against cancer. Nanoparticles containing targeted moiety have emerged as a cornerstone in cancer therapy. However, nano-cargo-based targeted therapy mainly involves biological molecules, such as nucleic acids, proteins, and immunomodulators, which target the mechanism involved in deranging cancer. Therefore, these biologically active molecules and their drug products require long-term stability inside and outside the body that can be enhanced using lyophilization and molecular recognition techniques. The paper attempts to provide a general overview of medication administration via nanoparticles for targeted cancer treatment and the effect of lyophilization on the stability of the formulation. This comprehensive review explores cutting-edge advancements in the fabrication of nanoparticles with an extensive range of methods and updated insights into lyophilization to improve the physicochemical characteristics of nanoparticles. The lyophilized process' development, scaling up, and transfer necessitate a number of NP formulation considerations as well as an optimized freeze-drying procedure to provide a high-quality cancer product. The review highlights the critical findings of <span class=
Keywords: immunomodulators